The Employee Welfare Program in PT. Royal Coconut Gorontalo District - Dian Fitriani Karim (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The purpose of this study was to determine the employee welfare program in PT. Royal Coconut Gorontalo district. The method used was qualitative, data was collected through observation, interviews and literature studies. The number of informants was 20 people. The data obtained relates to the welfare of the employees of PT. Royal Coconut, Gorontalo District, which was then analyzed through categorization and data reduction. The results showed that the theory put forward by Hasibuan about the types of welfare programs when compared with the welfare programs implemented at PT. Most of Royal Coconut is still not in accordance with what is happening in the field due to the fact in the research location that the employee welfare program has not been maximally implemented in terms of economics such as pension, food and transport fees. In terms of facilities such as arts, education funds, and cooperative activities and in terms of services such as pickups, babysitting, legal assistance, financial advisors, insurance and home loans, as well as free health clinic services in companies, they still tend to be limited due to insufficient supply of medicines and doctors and nurses who are often not in the clinic during employee working hours. From the results of the study concluded that the employee welfare is not good because PT. Royal Coconut has not implemented maximum employee welfare services in terms of economy, facilities, and welfare services.